GENETIC VARIABILITY OF GIANT GOURAMY STRAINS REVEALED BY RANDOM AMPLIFIED POLYMORPHISM DNA - Estu Nugroho (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2013)
Genetic variability of giant gouramy strains has been observed using RAPD Marker. Genomic DNA was extracted from giant gouramy fin clip, and amplified using primers OPA 1-20. There was no significant difference among three strains of giant gouramy analyzed. Based on two primers of RAPD (OPA 4 and 7), the highest variability was observed in Bluesafir with heterogeneity value of 0.3050 and followed by Paris (0.2832) and Soang (0.2360) respectively. The average of Nei’s genetic distance is 0.118, and the smallest on is between Paris and Bluesafir.